2018
DOI: 10.1128/mbio.02293-17
|View full text |Cite|
|
Sign up to set email alerts
|

CLAG3 Self-Associates in Malaria Parasites and Quantitatively Determines Nutrient Uptake Channels at the Host Membrane

Abstract: Malaria parasites increase host erythrocyte permeability to ions and nutrients via a broad-selectivity channel known as the plasmodial surface anion channel (PSAC), linked to parasite-encoded CLAG3 and two associated proteins. These proteins lack the multiple transmembrane domains typically present in channel-forming proteins, raising doubts about their precise roles. Using the virulent human parasite, we report that CLAG3 undergoes self-association and that this protein's expression determines channel phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 49 publications
(72 reference statements)
2
47
0
1
Order By: Relevance
“…The proteins encoded by these clag3 alleles are more than 90% identical, with most of the variation present in a small hypervariable region near the C-terminus (HVR, S1A Fig). The unique HVR sequence of the Dd2 CLAG3.1 protein is responsible for PSAC block by ISPA-28 in this laboratory clone and lack of activity against channels from other parasite lines [15,37]. In keeping with this, we found that ISPA-28 is ineffective against 7G8 and GB4 channels ( Fig 1B and S1B Fig).…”
Section: Copy Number Reduction Permits High Confidence Genetic Mappinsupporting
confidence: 78%
See 3 more Smart Citations
“…The proteins encoded by these clag3 alleles are more than 90% identical, with most of the variation present in a small hypervariable region near the C-terminus (HVR, S1A Fig). The unique HVR sequence of the Dd2 CLAG3.1 protein is responsible for PSAC block by ISPA-28 in this laboratory clone and lack of activity against channels from other parasite lines [15,37]. In keeping with this, we found that ISPA-28 is ineffective against 7G8 and GB4 channels ( Fig 1B and S1B Fig).…”
Section: Copy Number Reduction Permits High Confidence Genetic Mappinsupporting
confidence: 78%
“…PSAC activity is essential for intracellular parasite growth and replication as it functions in nutrient uptake from host plasma [14,20]. Although originally proposed to result from upregulation of transporters endogenous to the erythrocyte, many studies have now linked PSAC activity to a parasite-encoded RhopH protein complex consisting of CLAG3, RhopH2, and RhopH3 [12,20,21,37]. The present studies provide three new insights into the role of CLAG3 in PSAC formation and intracellular growth of malaria parasites.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Similarly, a rhoptry bub location does not preclude roles during invasion, since the rhoptry bulb protein RhopH3, a component of the high molecular weight (HMW) RhopH complex, is important for RBC entry [22]. In contrast, RhopH3 and its partner proteins RhopH1/Clag and RhopH2 have additionally been shown to be involved in nutrient uptake during development of the intracellular parasite [22][23][24][25], whilst the rhoptry bulb low molecular weight (LMW) RAP1/RAP2 complex has been implicated in PVM formation [26]. In Toxoplasma (but not in Plasmodium) several rhoptry bulb proteins are enzymes, including proteases, phosphatases and kinases or pseudokinases, the latter two groups of which dramatically modulate host cell STAT signalling and the immunity-related GTPase (IRG) pathway involved in controlling parasite replication, and play key roles in virulence [27,28].…”
Section: Introductionmentioning
confidence: 99%